Relations of Digital Vascular Function, Cardiovascular Risk Factors, and Arterial Stiffness: The Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil) Cohort Study - Brant, Luisa C. C. (J Am Heart Assoc, 2014)
BACKGROUND: Vascular dysfunction is an early expression of atherosclerosis and predicts cardiovascular (CV) events. Peripheral arterial tonometry (PAT) evaluates basal pulse amplitude (BPA), endothelial function (PAT ratio), and wave reflection (PAT‐AIx) in the digital microvessels. In Brazilian adults, we investigated the correlations of PAT responses to CV risk factors and to carotid‐femoral pulse wave velocity (PWV), a measure of arterial stiffness. METHODS AND RESULTS: In a cross‐sectional study, 1535 participants of the ELSA‐Brasil cohort underwent PAT testing (52±9 years; 44% women). In multivariable analyses, more‐impaired BPA and PAT ratios were associated with male sex, higher body mass index (BMI), and total cholesterol/high‐density lipoprotein. Higher age and triglycerides were related to higher BPA, whereas lower systolic blood pressure, hypertension (HTN) treatment, and prevalent CV disease (CVD) were associated with lower PAT ratio. PAT‐AIx correlated positively with female sex, advancing age, systolic and diastolic blood pressures, and smoking and inversely to heart rate, height, BMI, and prevalent CVD. Black race was associated with lower BPA, higher PAT ratio, and PAT‐AIx. Microvessel vasodilator function was not associated with PWV. Higher PAT‐AIx was modestly correlated to higher PWV and PAT ratio and inversely correlated to BPA. CONCLUSION: Metabolic risk factors are related to impaired microvessel vasodilator function in Brazil. However, in contrast to studies from the United States, black race was not associated with an impaired microvessel vasodilator response, implying that vascular function may vary by race across populations. PAT‐AIx relates to HTN, may be a valid measure of wave reflection, and provides distinct information from arterial stiffness.